Writing: the re-construction of language. (March 2019) - Davidson, Andrew
Abstract: This paper takes as its point of departure David Olson's contention (as expressed in The Mind on Paper, (2016) CUP, Cambridge) that writing affords a meta-representation of language through allowing linguistic elements to become explicit objects of awareness. In so doing, a tradition of suspicion of writing (e.g. Rousseau and Saussure) that sees it as a detour from and contamination of language is disarmed: writing becomes innocent, becomes naturalised. Also disarmed are some of the concerns given rise to by the observation made in the title of Per Linell's book of a 'written language bias in linguistics' (2005, Routledge, London) with its attendant criticisms of approaches (e.g. Chomsky's) that assume written language to be transparent to the putative underlying natural object. Taking Chomsky's position (an unaware scriptism) as a representative point of orientation and target of critique, the paper assembles evidence that problematises the first-order, natural reality of cardinal linguistic constructs: phonemes, words and sentences. It is argued that the facticity of these constructs is artefactual and that that facticity is achieved by way of the introjection of ideal objects which the mind constructs as denotations of elements of an alphabetic writing system: the mental representation of language is transformed by engagement with writing and it is this non-natural artefact to which Structuralist/Generativist linguistics has been answering. Evidence for this position from the psycholinguistic and neurolinguistic literature is presented and discussed. The conclusion arrived at is that the cultural practice of literacy re-configures the cognitive realisation of language. Olson takes writing to be a map of the territory; however, it is suggested that the literate mind re-constructs the territory to answer to the features of the map. Highlights: The facticities of the phoneme, word and sentence are artefacts of alphabetic writing. Chomskyan linguistics answers to these artefacts, they are not natural kinds. Writing is a cognitive niche which transforms mental representations of language.